Identifying Musculoskeletal Pain Generators Using Clinical PET - Yoon, Daehyun; Kogan, Feliks; Gold, Garry E.; Biswal, Sandip (Seminars in Musculoskeletal Radiology, 2020)
Identifying the source of a person's pain is a significant clinical challenge because the physical sensation of pain is believed to be subjective and difficult to quantify. The experience of pain is not only modulated by the individual's threshold to painful stimuli but also a product of the person's affective contributions, such as fear, anxiety, and previous experiences. Perhaps then to quantify pain is to examine the degree of nociception and pro-nociceptive inflammation, that is, the extent of cellular, chemical, and molecular changes that occur in pain-generating processes. Measuring changes in the local density of receptors, ion channels, mediators, and inflammatory/immune cells that are involved in the painful phenotype using targeted, highly sensitive, and specific positron emission tomography (PET) radiotracers is therefore a promising approach toward objectively identifying peripheral pain generators. Although several preclinical radiotracer candidates are being developed, a growing number of ongoing clinical PET imaging approaches can measure the degree of target concentration and thus serve as a readout for sites of pain generation. Further, when PET is combined with the spatial and contrast resolution afforded by magnetic resonance imaging, nuclear medicine physicians and radiologists can potentially identify pain drivers with greater accuracy and confidence. Clinical PET imaging approaches with fluorine-18 fluorodeoxyglucose, fluorine-18 sodium fluoride, and sigma-1 receptor PET radioligand and translocator protein radioligands to isolate the source of pain are described here.
Keywords: pain; imaging biomarkers; inflammation; molecular imaging; positron emission tomography/magnetic resonance imaging (PET/MRI)